2013
DOI: 10.1208/s12249-013-0012-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cross-linking and Drying Method on Drug Delivery Performance of Casein–Pectin Microparticles

Abstract: Abstract. Pectin is a heteropolysaccharide which has been investigated for the development of colonspecific drug delivery systems. Polymers have been associated with pectin to reduce its aqueous solubility and improve the performance of drug delivery systems. Pectin-casein interaction is widely known in food research, but it has not been fully considered by pharmaceutical scientists. Thus, this study investigated the potential of casein-pectin microparticles as a drug delivery system and clarified the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Likewise, the intensity and peak location of amine groups at 672–910 cm −1 area triggered by the twisting vibration were altered in the coating, demonstrating the presence of N–H groups. The strength of carboxylate groups (1,385 cm −1 ) in CP‐SD‐SLNs reduced because the carboxylate groups contributed to the coating process (Marreto, Ramos, Silva, Freitas, & de Freitas, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the intensity and peak location of amine groups at 672–910 cm −1 area triggered by the twisting vibration were altered in the coating, demonstrating the presence of N–H groups. The strength of carboxylate groups (1,385 cm −1 ) in CP‐SD‐SLNs reduced because the carboxylate groups contributed to the coating process (Marreto, Ramos, Silva, Freitas, & de Freitas, ).…”
Section: Resultsmentioning
confidence: 99%
“…Free CMN exhibited −OH stretch vibration at 3,324.68 cm −1 and 3,015.16 cm −1 owning the presence of two hydroxyl groups, and the peaks exhibited at 1,742.37, 1,629.55, 1,597.73, and 1,507.1 cm −1 for the existence of carbonyl groups in its structure (Firman, Lisa, Raffaella, & Neil, 2017 Likewise, the intensity and peak location of amine groups at 672-910 cm −1 area triggered by the twisting vibration were altered in the coating, demonstrating the presence of N-H groups. The strength of carboxylate groups (1,385 cm −1 ) in CP-SD-SLNs reduced because the carboxylate groups contributed to the coating process (Marreto, Ramos, Silva, Freitas, & de Freitas, 2013).…”
Section: Temmentioning
confidence: 99%
“…19 Furthermore, similar principles were proposed by Luo et al 20 and successfully used in formulation of casein/pectin nanocomplexes as potential oral delivery vehicles. Nandy et al 7 used a combination of the release retardant ethyl cellulose and Eudragit RS 100 mixed with Eudragit S100 to produce microparticles by a quasi-emulsion solvent diffusion technique.…”
Section: Introductionmentioning
confidence: 82%
“…Furthermore pH‐sensitive Eudragits, that is, Eudragit L or Eudragit S, were used to encapsulate indomethacin by applying an emulsion–solvent evaporation method . The need to combine different polymers to encapsulate indomethacin was evident in Marreto et al ., that used pectin cross‐linked with casein, to reduce its aqueous solubility in order to achieve a better encapsulation efficiency, as polymer in microparticles prepared by coacervation and then dried by spray or spouted bed methods . Furthermore, similar principles were proposed by Luo et al .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that pectin-based polymers were discovered as having a novel potential to create highly technological materials with enhanced characteristics. Casein–pectin as a multiple-unit drug delivery system was designed for the colonic drug delivery of two model drugs with different solubilities: acetaminophen (PCT) and indomethacin (IND) [130]. The effect of chemical cross-linking and the drying method (spouted or spray-drying) on in vitro drug release, microcapsule digestibility, and structural integrity was investigated.…”
Section: Pectin As Carriers For Drug Deliverymentioning
confidence: 99%